(untitled) (Economic and Political Thought, 2016)
The article is a follow-up to the analysis of theoretical premises of command/ planned economy and presents practical consequences of the implementation of Marxism and Russian Bolshevism. The author discusses the phenomena resulting from practical use of the ideology starting with a statement about the “economic expansion drive” – a major determinant of decision-making factors in the command system. The economic expansion drive, which was a result of the system’s belligerent attitudes, made communist authorities take economic decisions in compliance with political criteria, irrespective of economic rationalism. As a result, all the efficiency indices in that system were poorer than in market economy. Practical effects of that also consisted in deformation of investment processes and defective consumer goods market manifesting itself in the form of invariable supply-demand disequilibrium. Political motives behind economic decisions also led to excessive use of resources and intensification of the “deficit” phenomenon in all the economic sectors. Practical consequences of the deficit were disastrous for companies’ efficiency and people’s financial situation. Finally, the author illustrates his theses with some data showing that from the 1970s the command system was sliding down an inclined plane and, at its end, it eventually collapsed.